Fresno Merced Counties Legal Services Staff at Roger Rocka's Guys and Dolls Show - Watkins, Howard::::::::: (1981)
Mary Ludy, Ann Higgins, Janice Pearson, Kurt Hoff, Bob Higgins, Elaine Harris at table